2004
DOI: 10.2214/ajr.182.3.1820619
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Small Pancreatic Tumors with Multiphasic Helical CT

Abstract: Thin-section contrast-enhanced helical CT is sensitive and highly specific for the detection of pancreatic tumors measuring 2 cm or smaller. Improvement in the detection rate of this technique compared with previous techniques lies in the optimization of parenchymal enhancement during the pancreatic phase and the decrease in slice thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(107 citation statements)
references
References 12 publications
3
99
2
3
Order By: Relevance
“…Tumors, being hypovascular and less dense than the normal pancreas on CT , are best seen in this pancreatic phase (Fig. 7) [20,21]. The pancreatic phase also depicts the arterial anatomy very well.…”
Section: Ctmentioning
confidence: 91%
See 1 more Smart Citation
“…Tumors, being hypovascular and less dense than the normal pancreas on CT , are best seen in this pancreatic phase (Fig. 7) [20,21]. The pancreatic phase also depicts the arterial anatomy very well.…”
Section: Ctmentioning
confidence: 91%
“…There are several heritable disorders which are associated with an increased incidence of pancreatic ductal adenocarcinoma such as Peutz-Jeghers syndrome (132 times increased risk), hereditary pancreatitis (53 times increased relative risk); familial atypical multiple mole melanoma syndrome (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) times increased risk); familial pancreatic cancer syndrome (9-32 times increased risk) and hereditary breast and ovarian cancer syndrome-BRCA mutation (2-10 times increased risk) [4,5].…”
Section: Epidemiologymentioning
confidence: 99%
“…17 The sensitivity of CT in the detection of pancreatic tumors has improved in recent times and lies between 75% and 100% in different series, with a specificity of 70%-100%. [22][23][24][25][26][27][28][29] However, the smaller the tumor is, the less the CT sensitivity. It is reported that CT sensitivity for lesions measuring #2 cm is between 68% and 77% 23,25 and the accuracy close to 77%.…”
Section: Accuracy Of Mdctmentioning
confidence: 99%
“…MDCTA seems to be the technique of choice, permitting detailed evaluation of peripancreatic arteries and veins before therapeutic selection and design, specifically in borderline cases. 5,[11][12][13]16,17,19,21,23,[25][26][27]29,33,[36][37][38][39][40][41]44,45,[48][49][50]52,53,56,57,[63][64][65][66] …”
Section: Publication-based Evidencementioning
confidence: 99%
“…Although the sensitivity and accuracy of MDCT and MRI in diagnosis of pancreatic cancer have been improved significantly, it is still difficult to diagnosis at an early stage (Bronstein et al 2004;Kartalis et al 2009). The sensitivities and specificities were reported as 73%-94% and 95% for CT (DelMaschio et al 1991;Koito et al 1997), 85% and 96% for MRI (Ichikawa et al 2001).…”
mentioning
confidence: 99%